Decentralization and Humanization of Public Health Services - e Silva, Marlene Simões; do Lago, Pamela Nery; Pinto, Carolina Costa; Mendes, Renata Castro; Lisboa, Luciana de Morais; Rodrigues, Ronaldo Gomes; Pereira, Ana Paula Caetano; Batista, Luciana Moreira; Nascimento, Andréia Elias da Cruz; Freitas, Pablo Raphael de; Santos, Merilaine Isabel dos; Santos, Carla Renata dos; et al. (International Journal of Advanced Engineering Research and Science, 2022)
The public disservice in health has become part of the daily lives of citizens, even with public policies of humanization and decentralization of services, representing an exceptional milestone for Brazilian public health. Thus, this research will investigate the proposal for decentralization and humanization of services to users, in line with article 6 of the Federal Constitution of Brazil (1988), and the Universal Declaration of Human Rights. It consists of a bibliographic survey, in which it was investigated through the Virtual Library in Saúyde, in the SciELO, LILACS databases and in the national legislation portal, in which the laws, decrees and ordinances referring to the subject of the study were researched, since which aims to present a proposal for the decentralization and humanization of health services to users in Brazil. 17 publications were analyzed in full, which were suitable for the purpose of this review. The decentralization of health services in Brazil is an important advance, bringing autonomy to health regions and a more directed management towards the adequate allocation of public resources to health in the country. Despite the legal support, what is perceived in practice is still far from what was expected and there is a long way to go to reach the desired quality standard when it comes to humanization of care. It is concluded, then, that even if the current legislation, there is still an important path to be followed for the health services provided in our country, present the desired level of excellence.